Customer satisfaction with digital banking in Cambodia - Lykemtheng He; Hong Soun (Faculty of Business and Economics, University of Surabaya, 2025)
Over the past decade and accelerated by the COVID-19 pandemic, Cambodia’s banking sector has transformed dramatically, with digital tools reshaping how everyday Cambodians manage their finance. However, what truly drives satisfaction with these new touch point? This study aims to discovers the key factors shaping customer satisfaction in Cambodia’s digital banking landscape, focusing on ease of use, accessibility, security, customer support, and how users adapt to new technologies. Surveying 280 Phnom Penh residents aged 18 and above. Regression analysis revealed that all five factors significantly impact satisfaction, Customers prioritize security and privacy of transactions. Adaptation and accessibility driven by intuitive platforms and multi-channel access are equally vital. Beyond ease of use and support, proactive engagement from providers is essential. The findings aren’t just numbers, this can be a roadmap for banks. By prioritizing ironclad security, user-friendly designs, customer service improvement, and ongoing customer education, institutions can build trust, loyalty and enhance their customer satisfaction in a competitive market. This study doesn’t just add to global research on digital banking it paints a vivid picture of Cambodia’s unique challenges and opportunities, offering actionable insights for banks aiming to thrive in an era where customer experience is king.